The Change of Butonese Cultural Landscape in Negeri Kawa, Molucas - Syahadat, Ray March (KOMUNITAS: International Journal of Indonesian Society and Culture, 2017)
As a maritime ethnic, Butonese people migrated to some places. A rather large amount of them are in Province of Maluku, Indonesia. This study aims at investigating Butonese cultural landscape in their new migrant region. Is there any different? If this study also aims to know social interaction among ethnics and how it affects Butonese cultural landscape dynamics. This study took place in Negeri Kawa, western part of Seram Regency, Maluku Province, on November 2015. The method used in the study was a qualitative method with in depth interview by snowball and triangulation technique, observation participation, focus group discussion (FGD), and literature study. The result showed that there is a different between Butonese cultural landscape in Buton and Negeri Kawa. Stereotype, presumption, and prejudice to Butonese people also occur. However, it is not always negative because from those three things, the process of acculturation and adaptation as a form of respect and prevention of Butonese culture can occur in Negeri Kawa.